Liberalization And Car Manufacturing In Sea-4 - Rajah, Rasiah (Universiti Malaysia Sarawak, (UNIMAS), 2001)
Automobile assembly in Southeast Asia began with simple operations by Ford Motors in Singapore in 1926 (Chee and Fong, 1983) and General Motors in Indonesia in 1928 (Witoelar, 1983). Assembly of completely knocked down (CKD) units were started by Ford Motors in Singapore in 1930. The smallness of the Southeast Asian market and the lack of adequate infrastructure services inhibited significant growth in production until the end of colonialism. Much of the automobiles sold were imported until the post-colonial governments started introducing tariffs and local content policies to encourage import-substitution assemblies. Indonesia, Malaysia, Philippines and Thailand raised tariffs on completely built up (CBU) units to stimulate domestic assembly and reduce the foreign exchange constraint. The initial experience was not characterized by deliberate efforts to promote national car initiatives a la Japan and South Korea. The Philippines and Thailand continued without ownership discriminating policies, though, some companies were forced to allow local partners. Malaysia and Indonesia, however, began promoting national car production using foreign technology through tie-ups with foreign firms. Hence, special initiatives to shelter the production of local cars against foreign cars surfaced strongly since the 1980s and 1990s.